Does female economic empowerment promote development? - Pooja Balasubramanian; Marcela Ibanez; Sarah Khan; Soham Sahoo (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2019)
* The empirical evidence supports the view that female economic empowerment is key to end poverty and boost economic prosperity. * Key policies to promote development and reduce poverty are employment programs targeting female labor market participation, asset ownership and increased bargaining power of women within the household. * Social norms might limit the mobility of women and thereby prevent these effects from occurring. * The comparison of the effect of different interventions might be obscured by the lack of comparability in the measures used. * We recommend the adoption of a common framework for the analysis of the impact of interventions that promote female empowerment.
Keywords: 330